Local Alternative currencies: New opportunities in expanding local financial services - Lakócai, Csaba; Gál, Zoltán; Kovács, Sándor Zsolt (Public Finance Quarterly, 2023)
The paper examines local complementary currencies, a type of economic money substitute, as one of the local responses to financial globalisation. The most recent wave of local currencies implies that their operation is independent of the processes of financial globalisation, i.e. financialisation, and this is substantiated by the examples found both in developed and developing countries. This doesn’t mean that local currencies have similar features in different social and political environments; alternative financial services meant to decrease financial exclusion, which include local currencies, have different mechanisms of operation in regions with different levels of wealth. At the end of the paper, we provide a brief overview of the situation in Hungary, examining the factors that influence the complementary use of local currencies.